Relative bioavailability of manganese from its chloride, oxide and sulphate salts for broiler chickens - SUNDER, G SHYAM; GOPINATH, N C S; PANDA, A K; KUMAR, CH VIJAYA; RAO, S V RAMA (The Indian Journal of Animal Sciences, 2011)
An attempt has been made to establish the relative bioavailability of reagent grade manganese (Mn) from chloride (Cl2), oxide (O) and sulphate (SO4) salts for broiler chickens at 5 weeks of age. Each of these salts was supplemented at 100, 1000 or 2000 ppm to a basal diet (maize-soybean meal) in factorial pattern (3×3). Hubbard broiler chicks (270) were used in the trial by distributing them equally into 9 groups with 6 replicates of 5 chicks each, and housed in stainless steel battery brooders with raised wire floor. Each experimental group was fed ad lib. with one test diet from 8 to 35 days of age. Results showed that Mn salts did not influence body weight gain (BWG), leg abnormality scores (LAS), tibia weight or tibia ash, but MnCl2 significantly affected feed conversion ratio (FCR) and increased Mn concentration in tibia, liver and kidney tissues compared to the oxide and sulphate salts. Inclusion of Mn in diet at 2000–ppm level depressed BWG, FCR, tibia weight and tibia ash, while maintaining higher Mn retention in tissues. Interaction between MnCl2 and its levels of supplementation exhibited poor performance, possibly due to higher retention of Mn in tibia, liver and and kidney compared to oxide or sulphate salts. Between MnO and MnSO4, the later maintained moderately high Mn retention in bone over MnO and the vice versa in liver and kidney. It appeared from these results that Mn in sulphate form had moderate turnover in tissues than the other 2 salts, particularly in bone, which was desirable. Inclusion of MnCl2 in feed needs caution due to high turnover of Mn in tissues. Supplementation of MnCl2 at lower levels may be useful.